Democracy and Growth Nexus in Indonesia - Azwar Iskandar; Achmat Subekan (Muhammadiyah University Press, 2019)
The objective of this study is to analyze the causality between democracy and economic growth in Indonesia for the period of 1995 to 2017. More specifically, this paper also attends to investigate the existence of a long-run relationship between them. This study perform a multivariate cointegration test with political stability as a control variable and cross-check this long-run relationship with an autoregressive distributed lag (ARDL) model approach to cointegration. This study also use the Granger causality test within a vector error correction model (VECM) framework and estimate three different models using a non-linear specification: Ordinary Least Squares (OLS) estimation, Fully Modified OLS (FM-OLS) and Dynamic Ordinary Least Squares (DOLS). The results show cointegration among the variables specified in the model when political stability is taken into account. Indeed, for economic growth and democracy to move together in the long run, they need to be associated with political stability. The tests for Granger causality conducted show a long-run causality running from GDP and political stability to democracy. In other word, the economic growth and political stability Granger cause democracy. It is the economic performance that influences democracy and not the reverse. In short-run, there is neutrality causation between democracy and growth, democracy and political stability, growth and political stability. These results suggest that economic growth through strong institutions is a precondition for democratization.